2008
DOI: 10.1007/s12111-008-9063-4
|View full text |Cite
|
Sign up to set email alerts
|

Religious Coping and Pain Associated With Sickle Cell Disease: Exploration of a Non-linear Model

Abstract: The current study tested a non-linear model of religious coping among Black patients with Sickle Cell Disease (SCD). We predicted that moderate prayer and church attendance would be associated with less severe affective and sensory ratings of pain, lower levels of psychopathology, and less frequent care utilization. The participants were 67 SCD patients, mean age 36.82 ± 11.47 (range 18–70) of which 45% were men. Using ANOVA procedures, our results indicated a main effect for the frequency of prayer which show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 20 publications
0
20
0
Order By: Relevance
“…Prayer, when used as a means to relinquish control and responsibility for pain solutions, can negatively impact disability and perceived self control. 21,22 O'Connell-Edwards et al 23 found that the highest levels of psychopathology and affective reactions to pain were found in the highest frequency of church attendees and that moderate church attendees experienced a lower intensity of pain and psychopathology. It may be that the moderate use of religion and spirituality resources are a more effective tool for treating pain when the individual stil retains some form of self efficacy and responsibility, but also feels supported by their higher power.…”
Section: Spirituality Religion and Painmentioning
confidence: 99%
“…Prayer, when used as a means to relinquish control and responsibility for pain solutions, can negatively impact disability and perceived self control. 21,22 O'Connell-Edwards et al 23 found that the highest levels of psychopathology and affective reactions to pain were found in the highest frequency of church attendees and that moderate church attendees experienced a lower intensity of pain and psychopathology. It may be that the moderate use of religion and spirituality resources are a more effective tool for treating pain when the individual stil retains some form of self efficacy and responsibility, but also feels supported by their higher power.…”
Section: Spirituality Religion and Painmentioning
confidence: 99%
“…Chronic pain sufferers will seek relief through whatever gives them the ability to reduce their suffering, since for pain sufferers their primary goal would be to reduce their experience of pain Quality of life has not always correlated positively with religious activities. Prayer and worship frequency have been found in some studies to correlate with higher levels of psychopathology, disability, poorer quality of life, and higher levels of pain [53][54][55][56][57][58]. Rippentrop et al [54] assessed the relationship of pain to the spiritual and religious beliefs, practices, and experiences of 122 participants and found that personal prayer, bible study, and meditation were used more frequently by people in poor physical health.…”
Section: Religion Spirituality and Painmentioning
confidence: 99%
“…Prayer, when used as a means to relinquish control and responsibility for pain solutions, can negatively impact disability and perceived self control [53]. O'Connell-Edwards, et al [58] found that the highest levels of psychopathology and affective reactions to pain were found in the highest frequency of church attendees and that moderate church attendees experienced a lower intensity of pain and psychopathology. It may be that the moderate use of religion/spirituality resources are a more effective tool for treating pain when the individual still retains some form of self efficacy and responsibility, but also feels supported by their higher power.…”
Section: Religion Spirituality and Painmentioning
confidence: 99%
“…Common coping strategies utilised within this population range from those that are psychologically healthy (e.g., positive religious coping strategies) (McDougald et al, 2009;O'Connell-Edwards et al, 2009) to those that are maladaptive (e.g., substance abuse) (Bediako et al, 2011;Edwards et al, 2006;Falvo, 2005). The use of religion as a means of coping with the effects of SCD has become of great interest in the current literature.…”
Section: Introductionmentioning
confidence: 99%
“…Within the literature, religious coping has been defined in a number of ways, with some studies emphasising the behavioural aspects of the construct (Biggar et al, 1999;Cigrang, Hryshko-Mullen, & Peterson, 2003;O'Connell-Edwards et al, 2009;Pargament, Smith, Koenig, & Perez, 1998;Van Olphen et al, 2003;Wachholtz, Pearce, & Koenig, 2007). However, the authors utilised the following definition "efforts to understand and deal with life stressors in ways related to the sacred" as measured by the Brief Religious Coping Scale (RCOPE) (Pargament, Feuille, & Burdzy, 2011).…”
Section: Introductionmentioning
confidence: 99%